Trainability, persuasion, or coercion: a study of human–dog and human–wolf interactions in early life - Gwendolyn Wirobski; Gwendolyn Wirobski; Friederike Range; Laura Bonnet; Zsófia Virányi (Frontiers in Ethology)
Human–dog interactions are often ascribed to selection for increased cooperativeness during domestication, implying voluntary participation and mutual benefit. Alternatively, building on a possible selection for higher deference and submissive inclinations toward more dominant individuals (deferential behavior or super-dominance hypotheses), human–dog interactions might rather rely on following the human lead. Here, we compare three components of tractability, i.e., the willingness to comply with human directions, of young, hand-raised wolves and dogs using a set of behavioral tests to investigate their 1) trainability (coming when called with and without a distraction, following commands), 2) responsiveness to persuasion (fetch and retrieve a ball), and 3) readiness to accept coercion (brushing, muzzling, lying on the back while being petted). Based on the hypothesis that dogs show higher compliance with human directions than wolves, we predicted that dogs would respond to being called and follow learned commands faster than wolves. Dogs should also be more responsive to persuasion and accept coercion more readily than wolves. In contrast to our predictions, we found no difference between latencies of coming when called or when asked to sit, but wolves took longer to lie down on command than dogs. In the fetch and retrieve task, dogs retrieved the ball more often than wolves at 9 weeks of age, but not at 6 and 8 weeks, and it was more difficult to get the ball back from the wolves than from the dogs, at least when the partner was a stranger. Surprisingly, there were no significant differences between wolves and dogs in the brushing and the muzzling tests. In the final test, dogs accepted coercive handling when lying on their backs and remained lying down as long as without restraint, whereas the opposite was the case for wolves. In conclusion, the findings support the deferential behavior hypothesis whereby dogs more readily accept the leading role of the human partners, regardless of relationship strength and interaction style (persuasive vs. coercive), but wolves comply only if there is mutual trust and the interaction does not involve physical restrictions.